2020
DOI: 10.1088/1674-1056/ab96a2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stress-induced inhomogeneous electroluminescence in GaN-based green LEDs grown on mesh-patterned Si (111) substrates with n-type AlGaN layer*

Abstract: Inhomogeneous electroluminescence (EL) of InGaN green LEDs grown on mesh-patterned Si (111) substrate had been investigated. Sample with n-AlGaN inserted between the pre-strained layers and the first quantum well showed the inhomogeneous EL in the low current density range. Near-field EL emission intensity distribution images depicted that inhomogeneity in the form of premature turn-on at the periphery of the LED chip, results in stronger emission intensity at the edges. This premature turn-on effect significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…For GaN-based LEDs, it is suggested that electrical stress-induced degradation can be attributed to the generation or the propagation of point defects activated by carrier transport, such as vacancies or anti-site defects. [8][9][10][11][12] In addition, effects of dislocations on device degradation cannot be ignored for NUV LEDs [13][14][15] due to the lack of In-rich clusters that separate carriers from dislocations. [16] However, the behavior of defects that cause device degradation has yet to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…For GaN-based LEDs, it is suggested that electrical stress-induced degradation can be attributed to the generation or the propagation of point defects activated by carrier transport, such as vacancies or anti-site defects. [8][9][10][11][12] In addition, effects of dislocations on device degradation cannot be ignored for NUV LEDs [13][14][15] due to the lack of In-rich clusters that separate carriers from dislocations. [16] However, the behavior of defects that cause device degradation has yet to be confirmed.…”
Section: Introductionmentioning
confidence: 99%